Urban teens: Trauma, posttraumatic growth, and emotional distress among female adolescents. - Ickovics, Jeannette R; Meade, Christina S; Kershaw, Trace S; Milan, Stephanie; Lewis, Jessica B; Ethier, Kathleen A (Journal of consulting and clinical psychology, 2006)
Urban teens face many traumas, with implications for potential growth and distress. This study examined traumatic events, posttraumatic growth, and emotional distress over 18 months among urban adolescent girls (N = 328). Objectives were to (a) describe types of traumatic events, (b) determine how type and timing of events relate to profiles of posttraumatic growth, and (c) prospectively examine effects of event type and posttraumatic growth on short- and long-term emotional distress with controls for pre-event distress. Results indicate that type of event was related to profiles of posttraumatic growth, but not with subsequent emotional distress. When baseline emotional distress was controlled, posttraumatic growth was associated with subsequent reductions in short- and long-term emotional distress. Implications for future research and clinical practice with adolescents are addressed.
Keywords: Adolescent; Adult; Female; Follow-Up Studies; Humans; Incidence; Life Change Events; Mood Disorders; Prevalence; Prospective Studies; Questionnaires; Stress Disorders, Post-Traumatic; Urban Population